Factors associated with Dispensing Practices in Retail Pharmacies in Kampala District. A Cross-Sectional Study. - Nyombi, Joseph (Student’s Journal of Health Research Africa, 2022)
Background: There is a growing global problem of inappropriate dispensing practices in retail pharmacies for drugs including antibiotics and even controlled drugs. Therefore a study was carried out to assess the factors associated with dispensing practices of drugs in retail Pharmacies in Kampala district. Methodology: The study design was cross sectional analytical study and a sample of 385 respondents was selected using a simple random sampling technique and a questionnaire was used to collect data. Results: The study found out that majority (52.9%) of the pharmacies had inappropriate dispensing practices of drugs. The study also showed that majority (60.4%) of the retail pharmacies never had designated areas in their facilities for counseling of patients. The study also showed that about 30% of pharmacies which had a designated area for counseling of patients practiced appropriate dispensing practices of drugs as compared to those that never had designated areas for counseling. Majority (41.7%) of the dispensers in the retail pharmacies were Nurses and 53.4% of the dispensers had not participated in an in-service training program on dispensing medicine. The nature of the professional and frequency of previous in-service training program determined the dispensing outcomes. Conclusion: The study revealed that the inappropriate dispensing practices in pharmacies were attributed to; profession, experience of dispensing, having attended dispensing training and the frequency of attendance of training, having designated areas for counseling and presence of structures for reporting patient complaints. Recommendations: In order to improve on the appropriateness of dispensing practices in retail pharmacies, Regular in service training by supervising pharmacists should be enhanced. Pharmacies should designate counselling areas for patients and regulatory agencies, mainly NDA should increase supervision visits to pharmacies and ensure that dispensing guidelines are adhered to by all pharmacies.